Miniature miracle [videorecording] the computer chip - Jampel, Barbara; Kane, Dennis B.; Skinner, Thomas; National Geographic Society, Washington, D.C.; WQED (Television station : Pittsburg, Pa.). ([Washington, D.C.] The Society, 1985)
Documentary about progress in computer technology and its applications to everyday life. The new technological era is a miniature miracle - the computer chip, a power packed chip coupled with human ingenuity.
VHS.
Narrated by Alexander Scourley ; edited by Sandy Northrop, photographed by Bertram Van Munster, Norris Brock, Joe Seamans.
Keywords: Integrated circuits; Computers and civilization; Technology -- Social aspects